(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article presents new lexicon in the periodical issue “Catholic bulletin” in the word-forming aspect; the role of borrowings and new words in the development of lexical paradigma of modern Ukrainian language has been analysed in the article. The large number of borrowings is caused by tradition and history of development of the catholic church, by the world’s globalizating tendencies.